Translational medicine and drug discovery - Littman, Bruce H. 1944-; Krishna, Rajesh (New York Cambridge University Press, 2011)
"Focuses on the new discipline of translational medicine as it pertains to drug development within the pharmaceutical and biotechnology industry"--Provided by publisher.
Section I. Translational medicine: history, principles and application in drug development: 1. Translational medicine:definition, history, and strategies/ Bruce H. Littman -- 2. Translational medicine and its impact on diabetes drug development / Roberto A. Calle and Ann E. Taylor -- 3. Challenges in atherosclerosis / John S. Millar -- 4. Obesity: new mechanisms and translational paradigms / Gregory Gaich and David E. Moller -- 5. Bone disorders: translational medicine case studies / S. Aubrey Stoch -- 6. Case studies in neuroscience: unique challenges and examples / Gerard J. Marek -- 7. Translational medicine in oncology / Dominic G. Spinella; Section II. Biomarkers and public-private partnerships: 8. Biomarker validation and application in early drug development: idea to proof of concept/ Pfizer Global Research and Development, 2004 -- 9. Image biomarkers in drug development: case studies / Johannes T. Tauscher and Adam J. Schwarz -- 10. European new safe and innovative medicine initiatives: history and progress (through December 2009) / Ole J. Bjerrum and Hans H. Linden -- 11. Critical path institute and the predictive safety testing consortium / Elizabeth Gribble Walker -- 12. The biomarker consortium: facilitating the development and qualification of novel biomarkers through a precompetitive public-private partnership / David Wholley and David B. Lee; Section III. Future Directions: 13. Improving the quality and productivity of pharmacometric modeling and simulation activities: the foundation for model-based drug development / Thaddeus H. Grasela, Jill Fiedler-Kelly, and Robert Slusser -- 14. Embracing change: a pharmaceutical industry guide to the 21st century / Mervyn Turner.
Includes bibliographical references and index.
Keywords: Drug development; Molecular pharmacology; Drug Discovery; Translational Medical Research -- methods